The Impact of Tregs on the Anticancer Immunity and the Efficacy of Immune Checkpoint Inhibitor Therapies - González-Navajas, Jose M.; Fan, Dengxia Denise; Yang, Shuang; Yang, Fengyuan Mandy; Lozano-Ruiz, Beatriz; Shen, Liya; Lee, Jongdae (Frontiers in Immunology, 2021)
Although cancers arise from genetic mutations enabling cells to proliferate uncontrollably, they cannot thrive without failure of the anticancer immunity due in a large part to the tumor environment's influence on effector and regulatory T cells. The field of immune checkpoint inhibitor (ICI) therapy for cancer was born out of the fact that tumor environments paralyze the immune cells that are supposed to clear them by activating the immune checkpoint molecules such as PD-1. While various subsets of effector T cells work collaboratively to eliminate cancers, Tregs enriched in the tumor environment can suppress not only the native anticancer immunity but also diminish the efficacy of ICI therapies. Because of their essential role in suppressing autoimmunity, various attempts to specifically deplete tumor-associated Tregs are currently underway to boost the efficacy of ICI therapies without causing systemic autoimmune responses. A better understanding the roles of Tregs in the anti-cancer immunity and ICI therapies should provide more specific targets to deplete intratumoral Tregs. Here, we review the current understanding on how Tregs inhibit the anti-cancer immunity and ICI therapies as well as the advances in the targeted depletion of intratumoral Tregs.